Regression of colonic low grade B cell lymphoma of the mucosa associated lymphoid tissue type after eradication ofHelicobacter pylori. Issue 1 (1st January 2000) - Raderer, M; Pfeffel, F; Pohl, G; Mannhalter, C; Valencak, J; Chott, A
Abstract : BACKGROUND: Lymphoma of the mucosa associated lymphoid tissue (MALT) arising in the stomach has been shown to be related to Helicobacter pylori infection, and total regression of gastric lymphoma after successful eradication of H pylori has consistently been reported. MALT-type lymphoma at other localisations, however, has to our knowledge not been linked to H pylori, and eradication of the bacteria has not been studied for management of such lymphomas. PATIENT/METHOD: A 67 year old man was diagnosed with MALT-type lymphoma simultaneously involving the stomach and the colon descendens. In addition to the presence of MALT-type lymphoma, H pylori associated chronic gastritis was diagnosed, and treatment with clarithromycin, metronidazole, and omeprazole was initiated, resulting in its successful eradication. RESULTS: Follow up performed four months later showed regression of the colonic manifestation, whereas the gastric lymphoma did not respond to antibiotic treatment, as assessed by regular follow up for 14 months, in spite of its restriction to mucosa and submucosa. The patient was therefore treated with oral cyclophosphamide (100 mg a day) resulting in partial remission after seven months of continuous treatment. Because of the presence of residual lymphoma, additional irradiation was performed, which led to complete remission of the gastric lymphoma. The patient remains in complete remission 40 months after diagnosis and 26 months after initiation of treatment. CONCLUSION: In the case of concurrent gastric and intestinal low grade MALT-type lymphoma, H pylori eradication may cause regression of the intestinal lesion.